Psicossociologia das cidades: mudanças, seres humanos e sustentabilidade ampla nas cidades contemporâneas - Samantha de Oliveira Nery (2022)
This thesis aims to study and analyze, through theories and practices, dynamics of contemporary cities, seeking to identify modes of operation and variables that can stimulate the achievement of higher levels of broad sustainability, from a systemic view, including the relationship that citizens build with their respective cities. The current prospects for development towards a fairer life for the population are questioned, considering the world scenario full of enormous social inequalities, environmental destruction, among many other problems. One of the core axes of the research is the notion of broad sustainability, which has become a parameter for assessing cities and their living standards. Initially it will be presented its epistemological basis, which encompasses the assumptions of the systems: instability, complexity and intersubjectivity. Positive and negative feedback mechanisms are specified as significant regulation processes that may assist in desirable transformation processes. The notions of sustainability and sustainable development are then discussed, starting from a historical evolution, including the major world summits around those themes and some recent sustainable practices. From a complementary perspective, fundamental features of the human beings are presented, considering their social nature, such as the construction of identity and urban social identity, the appropriation of space and the constitution of social representations, bringing reflections on the relationship between people and between them and the environment. It also aims to address contemporary urban themes that describe the current context and help in its understanding, such as the processes of globalization, resources used in cities for their development, and common and vital aspects of urban life such as geography, urbanism and architecture, the economy, the legal framework, among others. In the empirical part of the work, three case studies will be developed, seeking to assess the levels of sustainable development achieved by each city, observing the conditions of its components - education, health, housing, economy, sports and culture, heritage, urbanism and architecture, different degrees of citizen participation, social representation and urban social identity, among others, based on triangulation, with qualitative and quantitative indicators. By reflecting on and studying the characteristics of the cities in an interconnected way, some patterns of success found in this environment are described, which make them more sustainable and humanized. As a conclusion, it is proposed the study and practice of the Psychosociology of Cities, in the broad understanding of cities and human beings with their multiple interrelationships, and by the monitoring and promotion of functioning mechanisms it can be constituted processes of permanence and change according to the chosen directions. The fundamental role of critical education and citizen participation in the constitution of a more sustainable world is also highlighted, as well as the involvement of all in this imperative processes of changes.